Effects of Individualized Dietary Phosphate Control Program With a Smartphone Application in Hemodialysis Patients in Taiwan. Issue 3 (July 2021) - Chiang, Yung-Chen; Chang, Ya-Ping; Lin, Ssu-Chin; Lin, Chin; Hsu, Pi-Hsiu; Hsu, Yu-Juei; Wu, Tsung-Jui
Background: Hyperphosphatemia in end-stage renal disease patients is prevalent and associated with increasing cardiac mortality. Restricting dietary phosphate intake is a key element in controlling hyperphosphatemia, but most patients fail due to lack of knowledge and sustainability. In this study, we aimed to examine whether incorporating a smartphone application (APP) into a multidisciplinary caring system can decrease the prevalence of hyperphosphatemia in hemodialysis patients. Methods: We designed a quasi-experimental study to enroll patients undergoing regular hemodialysis and assigned them to receive APP-assisted caring program (ACP group, n = 30) or standard education caring program (SCP group, n = 30). Both caring programs targeting dietary phosphate control were administered. Patients' general characteristics, self-care efficacy scales, knowledge test of phosphate control, and results of monthly blood biochemistry were analyzed. Findings: Knowledge of diet phosphate control and self-care efficacy were significantly higher in the ACP group. Notably, the knowledge improvement was higher in patients aged over 60 years. Compared to the SCP group, the percentage of patients with successful hyperphosphatemia control was significantly higher in the ACP group ( p = 0.0398). Conclusion: The APP-assisted caring program benefits patients with regular hemodialysis to achieve better dietary phosphate control without compromising proper protein intake.